Vagus nerve ultrasound in transthyretin familial amyloid polyneuropathy: A pilot study. Issue 2 (29th December 2021) - Du, Kang; Xu, Ke; Chu, Xujun; Tang, Yuwei; Lv, He; Zhang, Wei; Wang, Zhaoxia; Yuan, Yun; Meng, Lingchao
Abstract: Background and Purpose: Autonomic dysfunction is common in transthyretin familial amyloid polyneuropathy (TTR‐FAP). Because ultrasonography is a powerful tool to study peripheral neuropathy, vagus nerve (VN) ultrasonography was used in our study to investigate the possible changes of the dimension of VN in TTR‐FAP. Methods: Eighteen patients with TTR‐FAP and 17 age‐ and gender‐matched individuals without any neuropathies were enrolled in a pilot study. The cross‐sectional areas (CSAs) were measured bilaterally on transverse scans of vagus, median, and ulnar nerves. Clinical data were collected to explore the correlations with CSAs of VN. Results: The median CSAs of VN in TTR‐FAP were 3.5 (2.0‐6.0) mm 2 on the right side and 2.5 (1.0‐6.0) mm 2 on the left side, compared with 2.0 (1.0‐3.0) mm 2 and 1.0 (1.0‐2.0) mm 2 for healthy controls (HCs). There was a significant difference between the two groups on both sides ( p  < .001). The mean VN CSAs were correlated positively with the course of disease ( r = .7203, p = .0016)（not including the patient with the longest disease course), the Composite Autonomic Symptom Score 31 ( r = .5252, p = .0252), the left ventricular posterior wall thickness ( r = .5426, p = .0200), and the interventricular septum thickness ( r = .5103, p = .0305). The cutoff values of right and left VN CSAs to identify TTR‐FAP from HCs were 2.5 and 1.5 mm 2 and the areas under the curve were .9395 and .8856, with a high sensitivity (.889 and .889) and specificity (.941 and .765), respectively. Conclusion: VN enlargement is prevalent among TTR‐FAP patients. VN ultrasonography may be an important clinical tool for assessing the severity of autonomic dysfunction in TTR‐FAP.